Evaluation of Maize Varieties for Resistance to Northern Leaf Blight under Field Conditions in Ethiopia - Daniel Abebe; Narong Singburaudom; Somsiri Sangchote; Ed Sarobol (Agriculture and Natural Resources, 2008)
A study of reaction of thirteen maize varieties to northern leaf blight mainly caused by Exserhilum turcicum (Pass) Leonard and Suggs, were conducted at three locations Gambella, Abobo and Bako during 2003 and 2004 crop seasons. Variation among maize varieties was observed for several disease variables; the number of lesion, size, incidence, area under disease progress curve (AUDPC) and severity rating scale. In general, significant differences among genotypes were observed for data based on lesion number, size, AUDPC and severity rating scale at all locations. Susceptible varieties Gussau, Aboboko and Local- M had high AUDPC, large lesion size, fast onset of disease and many lesions in numbers. The host entries used in this study indicated that Kuleni was the most resistant to northern leaf blight across three locations, with low rating score. There was different response among varieties depending on disease intensity at each location. At Abobo, the final severity increased from 0.00 to 96.66% in 2003 and the results observed from 10.00 to 96.66% at Bako. However, at Gambella the incidence was as low as from 0.00 to 83.33%. Disease assessment methods were generally correlated with one another. Several varieties showed similaly significant reaction to disease in all locations. This meant that there was no virulent difference existing in the pathogen populations from location to location.